Mitigasi Bencana Tsunami Bagi Siswa SD Negeri 1 Latuhalat - Lawalata, Felix Fernando; Meilanny Cornelis; Velicia Ivena Hutubessy; Bireinda Tirza Violetta Tuapattinaya; Ronald Darlly Hukubun (Yayasan Literasi Sains Indonesia, 2022)
Disaster mitigation is an effort to minimize physical and material losses in the event of a disaster. This activity aims to provide insight and knowledge for early childhood about tsunami disaster mitigation. The method of service is by providing material on tsunami disaster mitigation with the hope that the participants who are students of SD Negeri 1 Latuhalat can apply what has been explained when the disaster occurs in order to minimize the loss of life.